The Principle of Public Relations in Leadership in Educational Institutions - Thahir, Ali Bin (International Conference of Moslem Society, 2019)
Leadership within specialized institutions in educational institutions has a very urgent function in facilitating comparative achievements among followers, also providing opportunities for them to develop and innovate. A leader also has an important role in the development of the institution he leads, where the leader becomes an effective communicator that he can actually establish a good communication relationship between personal leaders and followers, as well as those who do not only within the internal relations circle, however, a good relationship must extend beyond the institution's discussion room to the social discussion space around the institution because educational institutions are related to institutions that relate to the surrounding social community. A leader must be able to establish a good relationship between himself, his followers and also the social environment around the institution that might be more focused on the parents of the institution's students, so the principles of public relations must be needed in researchers in educational institutions, because the basis of success in social life is good communication between social individuals.